Combining microfluidics and FT-IR spectroscopy: towards spatially resolved information on chemical processes. Issue 6 (2nd September 2016) - Perro, Adeline; Lebourdon, Gwenaelle; Henry, Sarah; Lecomte, Sophie; Servant, Laurent; Marre, Samuel
Abstract : This review outlines the combination of infrared spectroscopy and continuous microfluidic processes. Abstract : This review outlines the combination of infrared spectroscopy and continuous microfluidic processes. FTIR spectroscopy gives access to the microscopic chemical composition of samples, which can be correlated with their macroscopic properties. This approach is widely used in chemistry or biology to get insights into reactive media. Meanwhile, the miniaturization of flow chemical reactors offers many advantages such as the small amount of products used or the versatility of the reactors. Coupling these two approaches creates major opportunities for the analytical field, although it raises additional challenges. Emphasis is placed on the most recent developments and limitations concerning the integration of infrared spectroscopy techniques within microfluidic devices, while current applications and future opportunities will be discussed.